Determinan Minat Berwirausaha Mahasiswa Fakultas Ekonomi dan Bisnis Islam UIN Syahada Padangsidimpuan - Haidir Harianja; Ya’ti Ikhwani Nasution (Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
Students from the Islamic economics and business faculty at UIN Syahada Padangsisimpuan have a high interest in entrepreneurship. So there are many students who have their own businesses, and some students who do not have an interest in entrepreneurship. The aim of this research is to determine and analyze the influence of the environment, education and income on the entrepreneurial interest of students at the Islamic Economics and Business Faculty of UIN Syahada Padangsisimpuan. This research is quantitative research. The data collection technique used was a questionnaire method which was obtained directly from respondents, namely students at the Islamic Economics and Business Faculty of UIN Syahada Padangsidimpuan. Analyzed using statistical tools, namely SPSS Version 22. Based on the results of multiple regression measurements, it shows that there is a simultaneous influence between the variables of education, environment and income on the interest in entrepreneurship of students at the Islamic Economics and Business Faculty of UIN Syahada Padangsisimpuan